(3LhGgQ GdcdGes - (3GdfLaj, GdCUagGfj, eMeO MSf Hf HGbQ Hf YHO GdQMje, J (B1266(3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj NJe GdTQGFY HGSegG (B...(3Efj bO QCjJ cJGH GdTQGFY ef eUfaGJ (B.. (3aj GdCMcGe GdTQYjI haQbGf aj GdYdhe GdabgjI aGFbG ef JbOeg EMGWI hLRGdI hGJaGbG (B..s
(3BNQgG (B:s
.. (3fYe GdQOI aj GdCKfGA fGbVI ddhVhAdahGJ GdGSJOGeI aj HYV GdCMhGd hdfLGSI eGA GdhVhA GdbGVj HaSGOg adh QLY aj GdCKfGA UM hVhDg (B...(3Je GdeLdO GdChds
(3JHUQI GdYfhGf (B:s
(3PcQg GdRQcdj ZdWG HGSe (B( (3LhGgQ GdCMcGe aj TQM TQGFY GdESdGe (B)s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\92s
(3GdPQjYI (B5\1306s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis